Listen and learn - Meiners, Cheri J., 1957-; Johnson, Meredith (Minneapolis, MN : Free Spirit, 2003)
Explains what listening means and provides examples of how listening can help with understanding, problem solving and safety. Includes information and extension activities for parents and teachers.
Book Links (A.L.A.)
Library Media Connection
2.9
K-3
K-3
Keywords: Attention -- Juvenile listerature; Listening -- Juvenile listerature; Social skills -- Juvenile listerature; Attention; Listening; Social skills; Attention; Interpersonal relations; Listening; Social skills